2021
DOI: 10.21037/atm-21-2574
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide promotes human trophoblast proliferation and migration through PI3K/Akt/mTOR signaling pathway

Abstract: Background: Preeclampsia (PE) is a complex pregnancy-related disease that endangers the safety of maternal and fetal. The purpose of this study is to reveal the pathogenesis of preeclampsia and discover new predictors from the perspective of peptidomics. The umbilical cord blood of PE and control group was analyzed by peptidomics. A peptide named Regulation of Proliferation Process in Preeclampsia (ROPPIP) was screened out to explore its role in the proliferation, migration and apoptosis of trophoblast cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, according to previous evidence, PI3K/Akt signaling pathway significantly contributed to the development of trophoblasts. 9 , 33 Herein, it was demonstrated that SNHG22 could activate PI3K/Akt signaling pathway to accelerate trophoblast migration and invasion via mediating miR-128-3p/PCDH11X. Although the authors displayed sufficient rationales to support the critical role of SNHG22 in promoting biological behaviors of trophoblasts, the authors’ findings remain to be further investigated by in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, according to previous evidence, PI3K/Akt signaling pathway significantly contributed to the development of trophoblasts. 9 , 33 Herein, it was demonstrated that SNHG22 could activate PI3K/Akt signaling pathway to accelerate trophoblast migration and invasion via mediating miR-128-3p/PCDH11X. Although the authors displayed sufficient rationales to support the critical role of SNHG22 in promoting biological behaviors of trophoblasts, the authors’ findings remain to be further investigated by in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
“… 7 In addition, it has been proved that trophoblast dysfunction significantly contributes to the induction of PE, 8 and increasing evidence has highlighted that normal proliferation and migration of trophoblasts can prevent PE. 9 , 10 Thus, it is necessary to identify indicators involved in the migration and invasion of trophoblasts for the prevention of PE.…”
Section: Introductionmentioning
confidence: 99%
“…PI3K/Akt, mTOR, and AMPK are serine/threonine kinases that play essential roles in regulating the proliferation and invasion of trophoblast cells and ameliorating placental oxidative stress in PE. [42][43][44] The Notch signaling pathway is a hypoxia-inducible pathway that is critical for placental formation, functions, and regulates trophoblast invasion. [45,46] Moreover, some of the 27 mRNAs have been reported to play essential roles in placental development.…”
Section: Discussionmentioning
confidence: 99%